VITAMIN B12 ADMINISTRATION FACILITATES THE ANTI-PSYCHOTIC AND PAIN-RELIEVING EFFECTS OF QUETIAPINE, IN THE ALZHEIMER PATIENTS WITH PSYCHOTIC SYMPTOMS - Vakilian, Alireza; Moghadam Ahmadi, Amir; Heidari, Moslem; Jalali, Nazanin; Nazer, Mohammad; Zare Bidaki, Mohammad; Hashemi, Seyed Meysam; Mirabzade, Mohammad; Rezaei, Amirreza; Amirteimoury, Morteza; Najmaddini, Pooria (Journal of Ayub Medical College Abbottabad, 2021)
Background: Psychotic symptoms in Alzheimer's disease (AD) patients are a problem in medicine. The efficacy of the vitamin B12 on the treatment of the psychotic symptoms of the AD patients in the association with antipsychotic drugs Quetiapine and Risperidone, was evaluated in this Study. Methods: The effects of vitamin B12 along with two other drugs were studied on the Mini-Mental State Examination (MMSE), Clinical Global Impression (CGI), Brief Psychiatric Rating Scale (BPRS) and pain Visual Analogue Scale (VAS) in 47 AD patients with psychotic symptoms, including 4 groups, psychotic AD patients treated with Risperidone, Risperidone plus vitamin B12, Quetiapine and Quetiapine plus vitamin B12. Results: The results showed that Quetiapine improved all of the psychotic criteria, while Quetiapine plus vitamin B12 had better results on BPRS after 2 weeks, VAS score and MMSE. Risperidone also improves all of the criteria except MMSE and drug efficacy index, while, vitamin B12 neutralize the effects of the Risperidone on the BPRS, VAS, and severity of illness. Conclusions: Due to these results, Quetiapine is the preferred antipsychotics drug and Vitamin B12 plays an effective role in treatment as an adjunct therapy.